Study on the releasing regularity of asphalt fume and its suppression technology - Guang Yang; Yongli Xu; Xiaolei Jiao; Yiming Li (PLoS ONE, 2025)
To reduce the unorganized release of asphalt fume during construction, a smoke suppressing and deodorizing (SSD) asphalt was prepared by adding smoke suppressants, which were styrene-butadiene-styrene (SBS), magnesium oxysulfate (MOS) whisker, and deodorant. The effect of smoke suppressants on the release amount of asphalt fume was investigated by mass method, and the effect of deodorant on the odor level of asphalt fume was evaluated by the odor intensity grading method. The results show that when the mass fractions of SBS, MOS and deodorant are 3%, 3% and 0.15%, respectively, 53% of asphalt fume can be effectively reduced, and the odor intensity grade can be significantly lowered. Based on FTIR and SEM analysis, the structural composition of modified asphalt was studied. It shows that SBS can break the dynamic balance of asphalt and produce an uneven network system, and whiskers interspersed in the asphalt play a role in regulating the thermal properties. Besides that, according to the results of thermogravimetry-mass spectrometry (TG-MS), the SSD asphalt can reduce the emission of volatile organic compounds and particulate matter during the high-temperature asphalt production process, with a significant inhibitory effect on small molecules.